Delft science in design 2 : conference proceedings, 4 April 2007 - Eekhout, Mick, 1950-; Tomiyama, T. (Tetsuo), 1957- (Research in design series, 2008)
The mission of the publication Delft Science in Designis to promote and advance the exchange of lessons learned on designbetween university and industry. Also, it aims to amplify thevisibility of the results of academic effort in design at DelftUniversity. The questions "What is design?", "What is engineering?", "What is science?" can be fiercely debated. Between the extremes ofartistic design and pure science, the transitions are like in fluid:they are smooth and gradual. An approach focusing on how the universitydeals with knowledge may provide a better entry to the debate. Themutual u.